Measurement properties of patient‐reported outcome measures for eczema control: a systematic review. (27th May 2021) - Stuart, B.L.; Howells, L.; Pattinson, R.L.; Chalmers, J.R.; Grindlay, D.; Rogers, N.K.; Grinich, E.; Pawlitschek, T.; Simpson, E.L.; Thomas, K.S.
Abstract: Atopic eczema (herein referred to as 'eczema') is a skin disease characterized by remitting and relapsing symptoms. The Harmonising Outcome Measures for Eczema (HOME) initiative was developed to establish a core outcome set (COS) for eczema to be measured for all future eczema trials. The core outcome set for atopic eczema clinical trials includes the domain for patient‐reported eczema control, but a review of the validation of available eczema control instruments was lacking. We aimed to review the literature and systematically assess the measurement properties of validated patient‐reported outcome instruments that capture eczema control. PubMed and Ovid EMBASE were searched up to 24 January 2020 for any study that reported on PROM instrument development or validation. The COnsensus‐based Standards for the selection of health Measurement Instruments (COSMIN) criteria were used to assess the quality of eligible studies. We screened 12 036 titles and abstracts and 58 full texts. A total of 12 papers were included, reporting on seven PROMS. These were assessed with respect to development, reliability, construct validity and responsiveness. Two instruments, Recap of Atopic Eczema (RECAP) and the Atopic Dermatitis Control Tool (ADCT), have been developed and validated to a sufficient standard to support their recommendation as patient‐reported outcome instruments for measuring control of atopic eczema as part of the HOME Core Outcome Set.